The Impact of Smartphone Applications on Language Learning and Teaching (A Literature Review) - Shahryar Banan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Technology continues to grow in importance as a tool to help teachers facilitate language learning for their learners. This study focuses on the role of using new technologies in learning. English as a second/foreign language. Rarely any younger person can now picture life without mobile devices. The aim of this review study is to examine whether mobile applications used as a foreign language for learning English are beneficial. The results reveal that mobile learning is becoming a salient feature of education as it is a great opportunity for foreign language learning. Its key advantages are: improving the learner's cognitive ability, Motivation of learners to study in both formal and informal settings, autonomy of the learner and Confidence, and the promotion of customized learning to support low-income students Attain the aims of their study. Although mobile learning appears to be eligible in general, it is desirable Plan, schedule and execute it with care, according to the needs of the students and include multiple Language competencies in realistic learning environments.